Importance of resilience among school children: Enhancing Resilience and Academic Success among Vulnerable Adolescents in Residential Care Facilities (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The capacity of a person to handle stress is influenced by their level of resilience. This researchwas carried out to aid in the creation of efficient preventative measures for high-risk adolescents residingin residential care facilities associated with the Bangalore Welfare Organization. The current research wasa descriptive analysis of 214 youths in 14 different government-run residential care facilities in the year2014. Convenience sampling was used to pick the study subjects. The necessary information wasobtained by means of the Wagnild and Young Resilience Scale, which has been shown to be both reliable(α=0.77) and valid (S-CVI=0.92). Descriptive and inferential statistics, such as the Chi-square test, theindependent t-test, and the analysis of variance (ANOVA), were used to the collected data in SPSS-20.With a mean score of 84.4111.01, the teenagers demonstrated remarkable levels of resilience. Studentsshowed resilience, and in univariate logistic regression analysis, characteristics including class,family type, time spent with father, time spent with mother, physical activities, and self-ratedschool success were linked to high levels of resilience. Overall, 46.2 of participants scored at themoderate level of resilience this was more common among female than male teenagers (P=0.006), andthe score was lower among elementary school students than among those in middle school and highschool (P0.001). Adolescents, especially boys, benefit greatly from preventative resilience-based tactics,which should be adopted by residential care facility directors and staff. Preventing teenage academicfailure and placing a higher importance on education than in the past requires a solid foundation.